2009
DOI: 10.1021/la9012697
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Encapsulated Gibbsite Nanoparticles: Efficient Preparation of Anisotropic Composite Latex Particles by RAFT-Based Starved Feed Emulsion Polymerization

Abstract: Anisotropic polymer-inorganic composite latex particles were synthesized by using a RAFT-based encapsulation approach on cationic gibbsite platelets. By using the RAFT agent dibenzyl trithiocarbonate, a series of amphipatic living random RAFT copolymers with different combinations of acrylic acid and butyl acrylate units were synthesized. These RAFT copolymers were used as living stabilizers for the gibbsite platelets and chain extended to form a polymeric shell by starved feed emulsion polymerization. Cryo-TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
1
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(154 citation statements)
references
References 32 publications
10
132
1
11
Order By: Relevance
“…In this work we used the RAFT dispersant PABA which is a random copolymer of acrylic acids (10 units) and butyl acrylate (5 units), which was first reported by Ferguson et al (2005) and used at several occasions either by the Hawkett group (Nguyen et al, 2008, 2013; Ali et al, 2009) or by our group (Das et al, 2011; Das and Claverie, 2012; Zhong et al, 2012). Other polymeric dispersants were also assessed, such as random copolymers of styrene and acrylic acid (Zhong et al, 2012) or homopolymers of acrylic acid (Daigle and Claverie, 2008), but they were found to be less efficient during the subsequent encapsulation, and they were not further investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we used the RAFT dispersant PABA which is a random copolymer of acrylic acids (10 units) and butyl acrylate (5 units), which was first reported by Ferguson et al (2005) and used at several occasions either by the Hawkett group (Nguyen et al, 2008, 2013; Ali et al, 2009) or by our group (Das et al, 2011; Das and Claverie, 2012; Zhong et al, 2012). Other polymeric dispersants were also assessed, such as random copolymers of styrene and acrylic acid (Zhong et al, 2012) or homopolymers of acrylic acid (Daigle and Claverie, 2008), but they were found to be less efficient during the subsequent encapsulation, and they were not further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Just prior use, acrylonitrile (AN) was passed over a column of basic alumina in order to remove the polymerization inhibitor. The random copolymer PABA, containing an average of five butyl acrylate and 10 acrylic acid units was prepared according to literature (Nguyen et al, 2008; Ali et al, 2009). Outmost care should be used to manipulate acrylonitrile which is highly toxic.…”
Section: Methodsmentioning
confidence: 99%
“…The strategy that we have been using relies on the adsorption of functional amphiphilic copolymers on the surface of the ceria nanoparticles, followed by emulsion polymerization. This strategy was recently reported by several groups (3)(4)(5)(6). Thus, we have synthesized different water-soluble amphiphilic complexing RAFT macro-agents containing carboxylic acid, sulfonic acid or phosphonic acid groups.…”
Section: Introductionmentioning
confidence: 94%
“…Reversible Addition Fragmentation Chain Transfer (RAFT) polymerization is a controlled radical polymerization technique which now has been developed for its applications in emulsion based systems [7][8]. Contrary to conventional free radical polymerization, RAFT offers an inherent advantage of control over molecular weight and the structure/composition of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to conventional free radical polymerization, RAFT offers an inherent advantage of control over molecular weight and the structure/composition of the polymer. The application of RAFT for the synthesis of controlled morphologies such as nanocapsules already resulted in few very promising approaches [7][8]. Recently, Ali et al reported a simple RAFT-based templating approach for the synthesis of water filled polymeric nanocapsules using vesicles [8][9].…”
Section: Introductionmentioning
confidence: 99%